“I Don’t Feel Like I’m Up Against a Wall of Men”: Negotiating Difference, Identity and the Glass Ceiling in Sports Information - Whiteside, Erin; Hardin, Marie (Journal of Intercollegiate Sport, 2011)
This research explores how women in college sports public relations cope with their minority status and the related notion of a glass ceiling in the workplace. Drawing from a socialist feminist perspective and Wrigley’s (2002) “negotiated resignation” model, we explore how these women negotiate the tension of working in an industry with a glass ceiling, arguing that many may deny a gender identity altogether, instead blaming discrimination on exterior factors or women themselves.